Family structure and oral habits among children age 1 to 12 years resident in ile-ife, Nigeria - Titus Ayodeji Oyedele; Kolawole Kikelomo; Morenike Folayan; Hakeem Agbaje; Elizabeth Oziegbe; Nneka Onyejaka; Nneka Chukumah (Universidade Estadual de Campinas, 2017)
Oral habits are repetitive actions that are done automatically. These behaviours are started and stopped spontaneously with or without deleterious effect on the developing occlusion. Aim: To explore the family related factors associated with oral habits in children resident in sub-urban Nigeria. Methods: A cross sectional study utilizing a household survey to recruit 992 1year to 12-year-olds. Information collected using a structured questionnaire included gender, family structure (parenting structure, birth rank, number of siblings, socioeconomic status) and types of non-nutritive habits. The association between family structures related variables and presence of non-nutritive oral habits was determined using Chi square. Logistic regression was used to determine the predictors of presence of oral habits. Results: There was no significant association between the prevalence of oral habits and parenting structure (p=0.52), birth rank (p=0.50) and socioeconomic status (p=0.14). However, the association between oral habits prevalence and number of siblings the child had was significant (p=0.03). The odds of having a non-nutritive oral habit reduced insignificantly for those from middle (AOR: 0.67; 95% CI: 0.42-1.08) and low (AOR: 0.96; 95% CI: 0.59-1.55) socioeconomic class when compared with those with high socioeconomic status; and for last born and only children (AOR: 0.94; 95% CI: 0.56-1.60) and children with 2-4 siblings (AOR: 0.62; 95% CI: 0.36-1.09) when compared with those that have more than 4 siblings. The odds were higher for children who were living with single parents or guardians (AOR: 1.41; 95% CI: 0.76-2.59; p=0.27) and for males (AOR: 1.21; 95% CI: 0.82-1.78). Conclusion: The study was unable to identify a significant family related predictor of presence of non-nutritive oral habits in the study population though a number of these factors increased the odds of having the habits. There is need to explore if specific family factors are associated with the presence of specific non-nutritive habits in this group of children.